The Doxorubicin-Induced G2/M Arrest in Breast Cancer Cells Modulated by Natural Compounds Naringenin and Hesperidin - Junedi, Sendy; Hermawan, Adam; Fitriasari, Aditya; Setiawati, Agustina; Susidarti, Ratna Asmah; Meiyanto, Edy (Indonesian Journal of Cancer Chemoprevention, 2021)
Doxorubicin as the common drug for breast cancer has been widely proposed to use in combine with a natural compound in order to overcome its side effects such as cardiotoxicity and resistance. Previously, we reported that naringenin and hesperidin, the abundant flavanons in citrus fruit peel, increased cytotoxic and apoptosis activities of doxorubicin in doxorubicin resistant breast cancer cells (T47D and MCF-7 cells). Since doxorubicin arrests G2/M phase in most cancer cells, both flavanons are speculated to affect the similar phase in breast cancer cells. Cell cycle distributions were determined by flowcytometry using propidium iodide (PI) to stain DNA of the cells. Combination of naringenin or hesperidin with doxorubicin increased accumulation of T47D cells in G2/M phase, while in MCF-7 cells, accumulated cells in G2/M phase were decreased, accompanying with slightly increased in G1 phase. Naringenin itself had no effect on cell cycle of both cells. Whereas, hesperidin arrested G2/M and G1 phases in T47D and MCF-7 cells, respectively. The different effect of naringenin and hesperidin in T47D and MCF-7 cells is most likely caused by difference of p53 status. In p53 mutant, T47D cells, naringenin and hesperidin supported mechanism of doxorubicin to arrest at G2/M that to be considered via p53-independent pathway. Whereas, in p53 wild-type MCF-7 cells, naringenin and hesperidin decreased G2/M arrest, suggesting that both flavanons do not utilize cell cycle arrest for their anticancer activity with doxorucibin. This study revealed that potential co-chemoterapeutic agents, naringenin and hesperidin distinctly modulated cell cycle arrest induced by doxorubicin according to the characteristic of breast cancer cells.Keywords: naringenin, hesperidin, doxorubicin, cell cycle, breast cancer cells.